Overview of transformative learning I: theory and its evolution. Issue 6 (1st November 2020) - Anand, Tejwansh S.; Anand, Shohreh V.; Welch, Marguerite; Marsick, Victoria J.; Langer, Arthur
ABSTRACT: This paper introduces ways that transformative learning is defined, conceptualized, practiced, and researched. Although such viewpoints share much in common, they differ based on context, culture, purpose, and process, among other things. Transformative learning is a living theory.